Performance of the Choledocholithiasis Diagnostic Score in Patients with Acute Cholecystitis - Gouveia,Catarina (2018)
Introduction: The prevalence of choledocholithiasis among patients with acute cholecystitis is estimated to be between 9 and 16.5%. There are no validated algorithms to predict choledocholithiasis in this group of patients. Aim: The aim of this study was to evaluate the performance of the choledocholithiasis diagnostic score proposed by the American Society for Gastrointestinal Endoscopy, in patients with acute cholecystitis. Material/Methods: A retrospective cross-sectional study, covering a 4-year period at a secondary care hospital, was performed. All patients with an encoded diagnosis of acute cholecystitis and with at least one of the following procedures were included: endoscopic retrograde cholangiopancreatography (ERCP), endoscopic ultrasound, magnetic resonance cholangiopancreatography, and intraoperative cholangiography. Results: Among 4,369 patients with the diagnosis of acute cholecystitis, 40 (0.92%) had clinical or sonographic suspicion of choledocholithiasis. Their mean age was 68.1 ± 15 years, and 22 (55%) were men. Thirty-one of the patients included (77.5%) had a high risk of choledocholithiasis, and 9 (22.5%) had an intermediate risk. In 16 (51.6%) of the 31 patients with a high risk, the diagnosis of choledocholithiasis was confirmed. In 2 (22.2%) of the 9 patients with an intermediate risk, the diagnosis of choledocholithiasiswas also confirmed. The high risk score for choledocholithiasis had a positive predictive value of 52% and a sensitivity of 89%. The intermediate risk score for choledocholithiasis had a positive predictive value of 22% and a sensitivity of 11%. Discussion and Conclusions: Suspicion of choledocholithiasis in patients with acute cholecystitis was a rare event (<1%). The sensitivity of the high risk score was approximately the same as found in published series with patients with suspected choledocholithiasis overall (86%), while the positive predictive value was substantially lower (52 vs. 79.8%). Therefore, in patients with acute cholecystitis and suspected choledocholithiasis, this score should not be used to screen for common bile duct stones, and a sensitive method should be used prior to ERCP.